Tinjauan Pengaplikasian Bahan Isolator : Penggunaan Bahan Isian Resin Epoksi Yang Terjangkau dan Optimal: Tinjauan Pengaplikasian Bahan Isolator : Penggunaan Bahan Isian Resin Epoksi Yang Terjangkau dan Optimal - Zaki Fairuz Ghani (Institut Riset dan Publikasi Indonesia, 2024)
Insulation materials come in various types and applications, leading to diverse pricing and effectiveness. One common type is epoxy resin, where the choice of filler materials can significantly impact its performance. Proper mixing can enhance the insulation's resistance to phenomena such as flashover, leakage current, and mechanical stress.This study conducted a literature review focusing on various filler materials, including rice husk ash, high-calcium sand, and corn cob ash. Experiments in the study examined leakage current and flashover characteristics of these insulation materials. The findings indicate that high-calcium sand can withstand higher conductive paths, corn cob ash exhibits stronger dielectric characteristics, and rice husk ash provides a more cost-effective filler option for insulation purposes.